Influence of quaternary conformation on the biological activities of the Asp49-phospholipases A2s from snake venoms - Magro, Angelo J. [UNESP] (2009)
One of the main components of snake venoms are the Asp49-phospholipases A2, also known as svPLA2s. The study of these toxins is a matter of great scientific interest due to their wide variety of biological effects. In this work we present strong evidences found in literature and other aspects which strengthen the importance of quaternary assembly for understanding the activities and molecular evolution of svPLA2s. © 2009 Bentham Science Publishers Ltd.